Negative Purification Method for the Selection of Specific Antibodies from Polyclonal Antisera - Cindy Benet; Pierre Van Cutsem (BioTechniques)
We developed a protocol to remove nonspecific antibodies from polyclonal antisera by adsorption on non-target antigens immobilized on nitrocellulose membranes. This “negative” purification method is simple and provides better immunoreagents than the blocking of nonspecific antibodies in solution or the enrichment of specific antibodies on nitrocellulose membranes. For routine applications, this method is quicker and cheaper than the purification protocols based on selective precipitations and affinity chromatography.